Efficacy of autologous platelet-rich plasma therapy versus topical Minoxidil in men with moderate androgenetic alopecia: a randomized open-label trial - Mithinkumar Balasundaram; Rashmi Kumari; Sivaranjini Ramassamy (Taylor & Francis Group, 2023)
Background Platelet-rich plasma (PRP) is an adjunctive treatment in androgenetic alopecia (AGA). Its role as a monotherapy, when compared to FDA-approved therapies in moderate grades of androgenetic alopecia is not established. Objectives We sought to study the efficacy and safety of standardized non-activated PRP preparation against topical minoxidil in AGA. Methods Men aged 20-50 with Grade III and IV (Modified Hamilton-Norwood) AGA were randomized to receive 5% Minoxidil (×6 months) or PRP injections (monthly ×3). The primary endpoints were global photographic assessment at week 24, change in target area hair counts, density, and anagen hair at week 12. Other outcomes were subjects' satisfaction and adverse events. Results In total, 64 participants were randomized. At week 24, 56% responded to Minoxidil arm and 38% to PRP (p = 0.124). There was a significant increase in target area hair count and density at week 12 within the groups. The difference between the groups was not statistically significant. Adverse events occurred in 53% and 37% of the PRP and minoxidil groups, respectively. Patient satisfaction was better with Minoxidil. Conclusion PRP is effective in the treatment of moderate grades of androgenetic alopecia in men, although perhaps not different from minoxidil. Side effects occur more frequently with PRP.